Comparison of Surface-Modified Adsorbents for Phosphate Removal in Water - Choi, Jae-Woo; Lee, Seung-Yeon; Lee, Sang-Hyup; Kim, Ji-Eun; Park, Ki-Young; Kim, Dong-Ju; Hong, Seok-Won (Kluwer Academic Publishers, 2012)
Three novel composite adsorbents, sulfate-coated zeolite (SCZ), hydrotalcite (SCH), and activated alumina (SCAA), were characterized and employed for the removal of phosphate from aqueous solution using equilibrium and kinetic batch experiments. Scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray diffraction spectrum were used to study the surface characteristics of the coated layer. Equilibrium tests showed that the adsorption of phosphate followed both Langmuir and Freundlich isotherms. The powder-type SCZ was better for phosphate removal (maximum binding energy, beta = 111.49 mg g(-1)) compared to hydrotalcite and activated alumina. The adsorption of phosphate was considered to take place mainly by ion exchange. The kinetic data followed a pseudo-second-order kinetic model. The initial adsorption of phosphate onto the sulfate-coated adsorbents was fast, indicating that the sulfate-coated materials developed in this study can be used as promising adsorbents for the removal of phosphate from wastewater or sewage.